We need to talk: a qualitative inquiry into pathways to care for young men at ultra-high risk for psychosis - Åmlid, Håkon Olav; Carlsson, Jan; Bjørnestad, Jone; Joa, Inge; Hegelstad, Wenche ten Velden (Frontiers in Psychology, 2024)
Introduction: It is known from the literature that men are slower to seek help and staying engaged in mental health care compared to women. Seeing that in psychosis, men more often than women have insidious onsets but also a more malign illness course, it is important to find ways to improve timely help-seeking. The aim of this study was to explore barriers and facilitators for help-seeking in young male persons struggling with early signs of psychosis. Methods: Qualitative interviews with nine young men who suffer from a first episode of psychosis or psychosis risk symptoms. Results: Male stereotypical ideals, significant others, and knowledge of symptoms and where to get help as well characteristics of symptom trajectories appeared to be important determinants of help-seeking behaviour. Discussion: Interviews indicated that help-seeking in the participants was delayed first, because of reluctancy to disclose distress and second, because significant others were unable to accurately recognize symptoms. Information, awareness, and easy access to care remain important in early detection and intervention in psychosis and psychosis risk. However, more emphasis should be placed on de-stigmatizing mental health problems in men and aiming information specifically at them.